1988
DOI: 10.1063/1.340085
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulation model of the effects of interface states on high-performance amorphous silicon solar cells

Abstract: A computer simulation model of amorphous silicon solar cells using a Scharfetter and Gummel solution of Poisson’s equation and Taylor and Simmons occupancy statistics for the dangling bond gap states (D states), has been developed. With a suitable choice of parameters, the numerical results for solar cell collection efficiency and dark and illuminated I-V characteristics agree well with experimental values. The model has been used specifically to study the influence of interface states at the TCO-p (transparen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(26 citation statements)
references
References 10 publications
0
26
0
Order By: Relevance
“…Due to the compositional disorder and morphological fluctuation at the i/p interface, a large amount of dangling bonds may exist and act as recombination centers or deep trapping centers [1]. Tasaki et al reported that the interface states cause abrupt band bending at the i/p interface and reduce the electric field in the i layer, consequently, the recombination rate near this interface region increases significantly [2]. For the purpose of improving the i/p interfaces of the a-Si:H solar cells, some methods have been developed including the application of a buffer layer inserted between the i-and p-layers.…”
Section: Introductionmentioning
confidence: 98%
“…Due to the compositional disorder and morphological fluctuation at the i/p interface, a large amount of dangling bonds may exist and act as recombination centers or deep trapping centers [1]. Tasaki et al reported that the interface states cause abrupt band bending at the i/p interface and reduce the electric field in the i layer, consequently, the recombination rate near this interface region increases significantly [2]. For the purpose of improving the i/p interfaces of the a-Si:H solar cells, some methods have been developed including the application of a buffer layer inserted between the i-and p-layers.…”
Section: Introductionmentioning
confidence: 98%
“…In case of the buffered cell with a 50 Å p/i interface section ͓Fig. 9͑b͔͒, the J sc is improved with increasing the N A of the buffer from 1ϫ10 18 cm Ϫ3 to 1ϫ10 19 cm Ϫ3 . Such an enhancement is caused by the stronger electric field due to higher N A .…”
Section: Numerical Analysis Of P-type Microcrystalline Si Bufferedmentioning
confidence: 98%
“…12. When the N A in the buffer is lower than the doping level of the pa-SiC:H (5ϫ10 18 cm Ϫ3 ), the buffer gives negative effects on the cell performance due to a lower electric field, resulting in the poorer V oc and FF than those of the bufferless cell. In case of the buffered cell with a 50 Å p/i interface section ͓Fig.…”
Section: Numerical Analysis Of P-type Microcrystalline Si Bufferedmentioning
confidence: 99%
See 1 more Smart Citation
“…Further more, in the case of p + -n-n + cell, the n-doping profiling in the absorber layer helps to get abrupt p + -n junction for high open circuit voltage. Since the carrier collection in the cell through p + layer with illumination is limited by electron transport than hole transport [32] and since the fill factor and the efficiency of the p-i-n cell are limited by the p/i interface recombination loss [33], the intentional n-doping in the absorber layer of a-Si:H based solar cell may have a critical role in determining the cell performance. However, dependence of doping concentration in the absorber layer on the photo parameters of the solar cell must be investigated in order to optimize the performance.…”
Section: Proposed Cell and Its Optimizationmentioning
confidence: 99%